Role of Urinary Tract Bacterial Infection in the Process of Bladder Carcinogenesis (Molecular and Biochemical Studies) - Ashmawey, Abeer Mostafa; Mohamed, Waleed S; Abdel-Salam, Ibrahim M; El-Gendy, Saad M; Ali, Ali I; El-Aaser, Abdelbaset A (Asian Journal of Medical Sciences, 2011)
Objective: This work is designed to study the possible role of chronic inflammation induced by E. coli in the urinary bladder of rats, the protective role of soybean flour, in addition to the role of oxidative and nitrosative stresses during bladder carcinogenesis. Material & Methods: This study was done on one hundred and fifty adult male albino rats (50 - 60 gm) that divided into five groups; a) Normal control group, b) Dibutyl amine and sodium nitrate treated group, c)E.Coli treated group, d) Dibutyl amine and sodium nitrate treated group plus E. coli, and e) Dibutyl amine and sodium nitrate treated group plus soy bean flour. Survival rate and histopatholgical changes during the period of treatment were recorded. Level of malondialdhyde, glutathione, catalase, hydrogen peroxide, Total anti-oxidant capacity and nitric oxide were measured. RNA extracted from bladder tissues was determined in addition to P16 level and caspase-3 expression. Results: Survival analysis showed a significant decrease (p< 0.001) in E.Coli and dibutyl amine plus sodium nitrate treated groups in comparing with the normal and other treated groups. Also, E. coli infection in the bladder tissues increases the carcinogenic ability of nitrosamine precursors, and enhances oxidative and nitrosative stresses via increasing levels of nitric acid, hydrogen peroxide and malondialdhyde. Regarding the molecular changes, extra bands have been found in E. coli and E. coli + carcinogen treated groups approximately at 16-18KD which are not present in the other groups. Conclusion: Bacterial infection of the urinary bladder may play a major additive and synergistic role in bladder carcinogenesis. Our results have also shown that soy bean flour may have a protective action during induction of urinary tumors. Key Words: Bladder carcinogenesis; E. Coli; Soybean; DBA; P16 DOI: 10.3126/ajms.v2i1.3542 Asian Journal of Medical Sciences 2 (2011) 31-40